Philosophy for the end of life: person, dignity, pain and hope of the dying man - Costanzo, Giuseppe (Studia Bioethica, 2016)
Identifying the theoretical frame for the development of a philosophy of the end of life is essential to highlight the value of man and the existential dimensions involved by this event. Moreover, it can help the people in charge of the palliative treatments to recognize the ethical principles underlying the value of life, to acknowledge the logicality of death and to ensure a medical care compatible with man and his identity. Person, dignity, hope and death are the starting points: they will be regarded from a double perspective, a theoretical and an empirical one. This works aims on the one hand to outline their meaning and their philosophical interpretation, on the other hand to try and sketch a cultural proposal synthesizing ethical principles and the contributions of experience. The first purpose is to identify in the definitions of person and dignity a few invariable fundamental concepts, which should be clearly recognizable and therefore applicable. The second purpose is to individuate the potentialities hidden in pain and hope, which could sustain the dying person during the final moments. All of this can be of great help for health professionals to direct their service to actual persons, beyond the strict medical aspect. This paper will approach the issue of the person through the thought of Luigi Pareyson, that of dignity through the ideas of Bernhard Casper and that of pain with the help of Viktor Frankl. The considerations on the hope of the dying man, on the contrary, are completely original. They do echo some thoughts of Salvatore Natoli, but they will try to give a new definition of the concept, basing on a triadic process. The main aim of the study, finally, is to encourage the organization of training courses for the teams working in hospices and RSAs. An intuitive understanding of the matter is not sufficient: it is necessary to complete work experiences with a theoretical approach, in order try and define a philosophy of life which is constantly evolving, since it is based on man and his meaning. The conclusions of this short essay are surely not definitive and they should be considered as part of a bigger picture, including also the physical, psychical and existential dimensions of the dying person.